Effect of Small Volume Blood Sampling on the Outcomes of Very Low Birth Weight Preterm Infants - Pin-Chun Su; Hao-Wei Chung; Shu-Ting Yang; Hsiu-Lin Chen (MDPI AG, 2022)
Very low birth weight (VLBW) preterm infants universally experience anemia of prematurity (AOP) while growing up. The effects of reduced blood sample volume on AOP, packed red blood cell (PRBC) transfusion, and outcome in VLBW preterm infants were examined in this study. To reduce blood loss due to phlebotomy, we set up a small volume blood sampling procedure in VLBW infants. In this retrospective study, we compared the VLBW infants who had undergone standard blood sampling (control group, n = 20) with those who underwent small volume blood sampling (study group, n = 84), with both groups receiving PRBC transfusion under restrictive criteria. Blood loss from phlebotomy and PRBC transfusion volume over 30 days was significantly lower in the study group than in the control group. Compared to the control group, hematocrit, reticulocyte, and iron levels were significantly higher in the study group. There were no significant differences in the proportion of patent ductus arteriosus, severe intraventricular hemorrhage, retinopathy of prematurity, and bronchopulmonary dysplasia between the two groups. The small volume blood sampling resulted in lower PRBC transfusion volume, less severe anemia, and greater bone marrow function at 30 days of age. This strategy can reduce potential adverse effects of PRBC transfusion in VLBW preterm infants.